TRAITS RELATED TO DROUGHT TOLERANCE IN TOMATO ACCESSIONS OF DIFFERENT GROWTH TYPE AND FRUIT SIZE - M. Brdar-Jokanović1; Z. Girek; S. Pavlović; M. Ugrinović; J. Zdravković (Journal of Animal and Plant Sciences, 2017)
This study was undertaken to investigate the possibilities for breeding drought tolerant tomatoes of different growth type and fruit size. The effects of drought were analyzed and the relationships among the observed traits at optimal irrigation and drought were interpreted using biplot analysis. Greenhouse pot experiment included 40 tomato accessions grown under optimal irrigation and drought (volumetric soil water content 35.0% and 20.9%), designed in complete randomized blocks. Observations were made at the intensive vegetative growth phase. The selection criterion for drought tolerance was plant dry weight. The accessions differed in: the whole plant, shoot and root dry weight, root proportion in plant dry weight (RP), plant height, number of leaves below the first flower branches (NL), number of lateral branches, and the first and second order lateral branches length. Drought resulted in significant decline, with the exceptions of the increased RP and NL. Determinate and indeterminate tomatoes were not significantly different in drought tolerance, implying that both types may be bred for tolerance to the stress; however, the accessions of larger fruit size had comparatively higher water requirements. Results of the biplot analysis indicated that drought tolerance in tomato does not necessarily have to be associated with robust root system and therefore the indirect selection strategy may rely on shoot traits.
Keywords: Biplot; drought; Lycopersicon esculentum; vegetative growth